RANCANG BANGUN SISTEM MONITORING SUHU TERINTEGRASI INTERNET OF THINGS PADA SOLAR HOME SYSTEM - Muhammad Hilmy Zharif; Muhammad Fauzan Edy Purnomo; Akhmad Zainuri (Jurnal Mahasiswa TEUB, 2022)
Clungup Mangrove Conservation (CMC) is a marine tourism area that has ecotourism principles. As an ecotourism place, of course, the CMC area needs development in terms of facilities, one of which is the provision of environmentally friendly electricity with alternative energy through solar cells. The solar cell system is placed in a box called the solar home system. This solar home system includes a solar charge controller, automatic switch, and inverter which when operating will produce hot air so that it has a high temperature and can affect the performance of the devices contained in the solar home system itself. So we need a temperature monitoring system so that the temperature at the Solar Home remains stable. This system is designed using a DHT11 temperature sensor which is controlled by an ESP8266 microcontroller. This ESP8266 is connected to the internet network so that sensor reading data can be sent to users via the Blynk application and QoS parameter measurements are also carried out from the ESP8266 to the Blynk server to determine the quality of data transmission. The test of sending data from ESP8266 to the Blynk server monitored through the Wireshark application has a delay of 196 ms, jitter of 196 ms at 0% packet loss, throughput of 2.84 Mbps. The use of a data package for 1 month with a calculation of 1 month consisting of 30 days obtained 1.41 GB.Keywords: Clungup Mangrove Conservation, Solar Home System, Temperature, IoT